2010
DOI: 10.5152/akd.2010.041
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic evaluation of systolic and diastolic heart function in patients suffering from beta-thalassemia major aged 5-10 years at the Zahedan Research Center for

Abstract: Objective: Cardiac complications are the major cause of morbidity and mortality in beta-thalassemia major. The aim of the study was to evaluate right (RV) and left (LV) ventricular systolic and diastolic functions using myocardial performance index in young, asymptomatic children suffering from thalassemia major, for early detection of cardiac function impairment, preventing further cardiac damage by modifying disease progression and treatment. Methods: A case-controlled, cross-sectional study involving 80 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…(19) Hemolytic anemia in thalassemia is also caused by unstable hemoglobin variants, (20) and heme iron released from hemolysis has been consistently associated with an increased risk of coronary heart diseases and cardiovascular mortality. (21) Other potential causes of hyperferritinemia are anoxia as a consequence of low hemoglobin level in the blood of patients with thalassemia. Ferritin concentration increases in response to stresses, such as anoxia.…”
Section: Resultsmentioning
confidence: 99%
“…(19) Hemolytic anemia in thalassemia is also caused by unstable hemoglobin variants, (20) and heme iron released from hemolysis has been consistently associated with an increased risk of coronary heart diseases and cardiovascular mortality. (21) Other potential causes of hyperferritinemia are anoxia as a consequence of low hemoglobin level in the blood of patients with thalassemia. Ferritin concentration increases in response to stresses, such as anoxia.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the risk of atrial and ventricular arrhythmias was increased in the patients with both congenital heart disease and pulmonary hypertension (4). It seems that in addition to iron overload, myocardial fibrosis, structural changes, and ventricular hypertrophy secondary to chronic anemia lead to heart failure in these patients (5). However, the early detection and treatment of heart failure due to any reason in patients with thalassemia major improve the prognosis and increase the life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…Although systolic dysfunction is investigated more commonly, reports about diastolic dysfunction are increasing [5][6][7].…”
Section: Cardiac Parameters In Thalassemia Major mentioning
confidence: 99%